Mitochondrial dynamics in the radiation response of cancer cells - Parker, Michelle (Department of Radiation Medicine, 2018)
Mitochondria are involved in the regulation of key cellular processes that determine the response of cells to damage. Mitochondrial fission and fusion are associated with cell cycle regulation, apoptosis, cellular bioenergetics and redox status, which contribute to cellular homeostasis and damage response. The study aimed to describe and correlate cancer cell mitochondrial features and inherent radiosensitivity, and to determine the effect of modulation of mitochondrial dynamics on radiation response using a fission inhibitor, Mdivi-1. Methods: Mitochondrial status in a number of cancer cell lines was characterised by assessment of mitochondrial morphology, respiration and membrane potential using MitoTracker® Red staining, respirometry and JC-1 ratiometric staining, respectively. Correlations with radiation sensitivity were performed. Radiation- and Mdivi-1-induced changes in mitochondrial morphology were also examined. Responses to various schedules of radiation and Mdivi-1 treatment were assessed using clonogenic survival. Microscopy was used to quantify apoptosis, micronuclei and mitotic features, while cell cycle dynamics were analysed using flow cytometry. Results: Notably, modulation of mitochondrial fission using Mdivi-1 significantly increased radiation response in A549 cancer cells. Mdivi-1 reduced fragmentation, increased membrane potential and induced cytotoxicity, cytogenetic damage, apoptosis and G2/M cell cycle arrest. However, with the exception of survival, sub-additive responses were consistently observed when Mdivi-1 was combined with radiation. Sub-lethal damage repair was unaffected by Mdivi-1. Characterisation of cancer cell lines revealed inherent diversity in radiation response and mitochondrial morphology, membrane potential and respiration, and several correlations were identified. Discussion and conclusions: Inhibition of mitochondrial fission was shown for the first time to enhance radiosensitivity in cancer cells, and to induce cytotoxicity. Mitochondrial modulators may therefore have therapeutic application. However, the sub-additive responses observed with Mdivi-1-radiation interactions suggest that optimisation of treatment scheduling may be important. The Mdivi-1-induced mitotic arrest may, in part, be responsible for the observed radiosensitisation, as cells accumulate in a radiosensitive cell cycle phase. In addition, the finding that Mdivi-1 treatment induced micronuclei suggested that the radiosensitisation may result from the interaction of cytogenetic damage induced by each agent. Overall, mitochondrial dynamics appears to significantly influence radiation response.